2006
DOI: 10.1097/01.rli.0000229773.11715.da
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Harmonic Intravascular Ultrasound

Abstract: These results indicate the feasibility of contrast harmonic intravascular ultrasound as a new technique for vasa vasorum imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…Some of these parameters may be accessible through intravascular imaging methods. [11][12][13][14][15][16][17][18][19] In addition, plaque type and morphology prior to intervention influence the long-term procedural outcome significantly. 20 Among the parameters that influence plaque vulnerability are the thickness of the fibrous cap overlying the necrotic core, inflammation, intraplaque hemorrhage, and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these parameters may be accessible through intravascular imaging methods. [11][12][13][14][15][16][17][18][19] In addition, plaque type and morphology prior to intervention influence the long-term procedural outcome significantly. 20 Among the parameters that influence plaque vulnerability are the thickness of the fibrous cap overlying the necrotic core, inflammation, intraplaque hemorrhage, and composition.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently applied this technique in studies in atherosclerotic miniswine (unpublished results) and demonstrated much improvement in contrast agent detection in the arterial wall. A number of studies have reported the use of harmonic (Goertz et al 2006), and subharmonic (Goertz et al 2007) and ultraharmonic (Maresca et al 2013) IVUS imaging with custom-made IVUS catheters for contrast-specific imaging, but those devices are not commercially available. In this study, we improved the validity of the analysis by careful matching of the aortic segments based on major branch points and landmark and analysis at multiple levels within the same aortic segment.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Unfortunately, predicting the risk for future acute cardiovascular events requires knowledge of plaque composition [7], which is not provided by conventional IVUS. Several IVUS signal processing techniques have been developed at an academic level to augment IVUS capabilities in detecting and characterizing coronary artery plaques at risk [8], [9] but failed to reach clinical practice so far.…”
Section: Introductionmentioning
confidence: 99%
“…Significant academic innovations such as IVUS flow [11], [12], IVUS palpography [8], [13], harmonic IVUS [14], [15] and contrast-enhanced IVUS [9], [16] were to date not taken up by industry. Furthermore, IVUS remains a niche technology, whose clinical practice did not vastly expand nor disappear.…”
Section: Introductionmentioning
confidence: 99%